AB0190 Assessment of plasma MICRO-RNA 155 in rheumatoid arthritis. (15th June 2017) - Negm, AA; Araby, S Al; Abdulazim, E; Raslan, H; Mohamed, K; Abdelhady, M; Hamed, M; Ismail, S
Abstract : Background: Several observations have indicated that Epigenetics now play a role in the pathogenesis of many diseases including Rheumatological and Immunological disorders such as Rheumatoid Arthritis.(RA). Unlike the genetic code, the epigenome is altered by endogenous (e.g. hormonal) and environmental (e.g. diet, exercise) factors and changes with age. There are three main and interrelated mechanisms: DNA methylation, post-translational modification of histone proteins and non-coding RNA which includes Micro RNA (miR). Objectives: 1. To determine the level of miR- 155 in plasma of RA patients. 2. To determine the potential value of miR-155 as molecular biomarker for diagnosis, prognosis of disease outcome, and prediction of therapeutic response in RA patients, and to test the relation miR-155 and serum levels of Matrix Metalloproteinase 3.(MMP) Methods: The study group consisted of 50 female RA patients in active disease and 25 controls of matched age and sex. Disease duration of 1 to 10 years and age range from 20 to 45 years old. They underwent detailed history taking including questionnaire for disability and health assessment scoring, clinical examination, radiological assessment by modified Sharp score. Routine laboratory investigations in addition to assessment of Plasma miR -155 expression levels and serum MMP-3 levels were done for all patients. Ten of the cases were resampled for miR-155 and MMP-3 after receiving treatment and entering disease remission (By DAS 28 score). Results: Plasma miR–155 expression levels and serum MMP-3 titers were significantly higher in RA patients than in controls (mean 4.071 and 1, p <0.001, mean 323.7 and 84.5, p <0.001) respectively. MMP-3 titers in serum were significantly higher in erosive than in non-erosive arthritis (mean 366.9 and 163.4, p <0.001). There was a significant positive difference between serum MMP-3 levels in disease activity and remission (mean 630 and 380, p <0.001). Mean values of the clinical parameters of our study group: STLW score (37.44±15.90), HAQ score (56.86±16.69), ACR disability class (2.224±0.872), DAS 28 score (4.856±1.222), ESR (58.16±29.44), Sharp score (32.36±23.9), There was a significant positive correlation between serum MMP-3 and DAS 28 score and ESR (r=0.022, p_0.022 and r=0.013, p=0.013 respectively). There was a significant positive moderate correlation between Plasma miR-155 and serum MMP-3 ( r =0.596, p <0.001). Correlation between Plasma miR-155 expression levels and HAQ (p=0.612, r=0.0744), with ESR (p=0.13, r=0.219) with DAS 28 score (p=0.187, r=0.192), with Sharp score (p=0.675, r=0.0797). Conclusions: miR-155 is indeed related to the presence of Rheumatoid arthritis, though not directly related to disease activity like MMP-3. miR-155 significantly but moderately correlates with MMP-3 in blood, but whether it plays a role in the pathogenesis of the disease with or without directly influencing MMP-3 in the joint will require more work on both markers inside the synovial fluid, synovial tissue and the synovial fibroblasts. MMP-3 was re-established in our study as a marker of disease activity and predictor of erosive arthritis. References: Annabelle Grolleau-Julius, Donna Ray, and Raymond L. Yung, The Role of Epigenetics in Aging and Autoimmunity, Clin Rev Allergy Immunol. 2010 Aug; 39(1): 42–50. Disclosure of Interest: None declared